Β-1, 3 glucan binding protein based selenium nanowire enhances the immune status of Cyprinus carpio and protection against Aeromonas hydrophila infection. Issue 83 (December 2018) - Iswarya, Arokiadhas; Vaseeharan, Baskaralingam; Anjugam, Mahalingam; Gobi, Narayanan; Divya, Mani; Faggio, Caterina
Abstract: In the present study, immunoenhancing effect of β-1, 3 glucan binding protein based selenium nanowire ( Ph β-GBP-SeNWs) in common carp, Cyprinus carpio was assessed. Biological based selenium nanoform was synthesized, using crustacean immune molecule β-GBP purified from the haemolymph of Paratelphusa hydrodromus. The morphological property of Ph β-GBP-SeNWs was analyzed through TEM which reveals, the synthesized nanowire exhibits approximately 30–50 nm width with smooth surface. For this current study, fish were fed with experimental diet includes Ph β-GBP, sodium selenite, selenomethionine and Ph β-GBP-SeNWs supplemented diet at different concentrations (0.5 mg, 1 mg and 2 mg) for 30 days. The growth performance, cellular and humoral immune responses (myeloperoxidase, reactive oxygen species, alkaline phosphatase and lysozyme activity) and antioxidant enzymes (glutathione peroxidase and catalase activity) in the fish fed with Ph β-GBP-SeNWs supplemented diet were significantly increased in dose-dependent manner, which was observed at two different interval period (15 th and 30 th day). Also, Ph β-GBP-SeNWs supplemented diet fed fish gain resistant after challenged with aquatic pathogen Aeromonas hydrophila and the relative survival percentage was increased. Agar disc diffusion and BacLight assay clearly demonstrated the antibacterial property of plasma of fish fed with Ph β-GBP-SeNWs supplemented diet against aquatic pathogen A. hydrophila, Vibrio parahaemolyticus and Vibrio alginolyticus . Moreover, confocal laser scanning microscopic analysis clearly showed that, Ph β-GBP-SeNWs supplemented diet fed fish plasma was more efficient in disrupting the architecture of bacterial colonies and thereby reduced the thickness of biofilm. Thus, the present study indicates that, incorporation of Ph β-GBP-SeNWs in the diet enhances the fish immune responses and disease resistance against aquatic pathogens. Graphical abstract: Highlights: β-GBP was purified from the Paratelphusa hydrodromus haemolymph. Ph β-GBP based selenium nanowires ( Ph β-GBP SeNWs) were synthesized and characterized. Ph β-GBP SeNWs supplemented diet and its impact on immune parameters were studied.